Mother Milk and the Indonesian Economy: A Major National Resource - Jon Eliot Rohde (Indonesian Pediatric Society, 1980)
While a myriad of health and nutritional considerations have proven that mother milk is the ideal infant food, national policy makers have failed to recognize the great value of human milk to the economy of developing countries. Today in Indonesia, mothers produce over one billion liters of milk annually with a conservatively estimated net market value of over Rp. 252 milyard or US S 400 million. Additional monetary savings in health and fertility reduction directly attributable to lactation add a further Rp. 75.6 milyard or US S 120 million to the economy. Mothermilk is one of Indonesia's most precious natural resources, exceeding tin and coffee in gross monetary value and approaching that of rubber. Its value exceeds twice the annual national budget for health and roughly equals the cost of imported rice, for which Indonesia has become, unenviably, the world's largest buyer. This great resource is not only renewable, but also equitably distributed, benefits consumer and producer alike and gives far ranging nonmonetery benefits to society. Positive governmental action is urgently needed to curtail private industry, professional groups and international assistance whose actions in providing and promoting milk of various kinds are insidiously depriving Indonesia of one of its greatest natural resources - Indonesian mother milk.